2018
DOI: 10.1111/bph.14425
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial endotoxin‐neutralizing peptides promote keratinocyte migration via P2X7 receptor activation and accelerate wound healing in vivo

Abstract: Our data suggest the potential application of Pep19-2.5 in the treatment of non-infected and S. aureus-infected wounds and provide insights into the mechanism involved in Pep19-2.5-induced wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…In this study, mice in the APs-L group had significantly promoted EGF secretion on day 7, but it can also be seen that they also had a certain effect on the proliferation of CD31 and FGF compared with the negative control group (Figure 5), which was different from the results of immunohistochemistry of topical APs. This may be caused by different mechanisms of action [23], or may also be because the healing of wounds in mice rather than humans is mainly achieved by contraction rather than epithelial re-epithelialization and granulation tissue formation, resulting in differences in action [45]. This accelerated skin wound healing in mice, consistent with the results of the healing rate, epithelialization time ( Figure 1 and Table 1) and H&E (Figure 4).…”
Section: Discussionsupporting
confidence: 69%
“…In this study, mice in the APs-L group had significantly promoted EGF secretion on day 7, but it can also be seen that they also had a certain effect on the proliferation of CD31 and FGF compared with the negative control group (Figure 5), which was different from the results of immunohistochemistry of topical APs. This may be caused by different mechanisms of action [23], or may also be because the healing of wounds in mice rather than humans is mainly achieved by contraction rather than epithelial re-epithelialization and granulation tissue formation, resulting in differences in action [45]. This accelerated skin wound healing in mice, consistent with the results of the healing rate, epithelialization time ( Figure 1 and Table 1) and H&E (Figure 4).…”
Section: Discussionsupporting
confidence: 69%
“…AMP gene expression increased during scratch wound healing. Endogenous AMPs have also been found to be upregulated in all stages of wound healing in vivo, indicating a role beyond microbial defense toward regulation of immune response, granulation tissue formation, and re-epithelization [ 82 , 83 ]. It was also observed that antimicrobial peptide transcript levels were significantly elevated after wIRA treatment under optimal conditions, further suggesting the involvement in the improved scratch wound healing outcome.…”
Section: Discussionmentioning
confidence: 99%
“…AMPs can promote wound healing [ 291 293 ] after skin injury, a process involving the complex interactions of keratinocytes, fibroblasts, vascular endothelial cells, immune cells and the extracellular matrix [ 294 296 ]. Some AMPs play a vital role in both skin barrier and function [ 297 ] and thus have the potential to treat multiple skin maladies, exemplified by melanoma, acne, diabetic foot ulcer and psoriasis [ 298 ].…”
Section: Activity Of Ampsmentioning
confidence: 99%